Establishment of a rapid, inexpensive protocol for extraction of high quality RNA from small amounts of strawberry plant tissues and other recalcitrant fruit crops - Christou, Anastasis; Georgiadou, Egli; Filippou, Panagiota S.; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2014)
Strawberry plant tissues and particularly fruit material are rich in polysaccharides and polyphenolic compounds, thus rendering the isolation of nucleic acids a difficult task. This work describes the successful modification of a total RNA extraction protocol, which enables the isolation of high quantity and quality of total RNA from small amounts of strawberry leaf, root and fruit tissues. Reverse-transcription polymerase chain reaction (RT-PCR) amplification of GAPDH housekeeping gene from isolated RNA further supports the proposed protocol efficiency and its use for downstream molecular applications. This novel procedure was also successfully followed using other fruit tissues, such as olive and kiwifruit. In addition, optional treatment with RNase A following initial nucleic acid extraction can provide sufficient quality and quality of genomic DNA for subsequent PCR analyses, as evidenced from PCR amplification of housekeeping genes using extracted genomic DNA as template. Overall, this optimized protocol allows easy, rapid and economic isolation of high quality RNA from small amounts of an important fruit crop, such as strawberry, with extended applicability to other recalcitrant fruit crops.
Keywords: Genomic DNA extraction; Fragaria × ananassa; Polyphenols; Polysaccharides; Protocol; Total RNA extraction